PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN TINDAK PIDANA PENIPUAN YANG DILAKUKAN SECARA BERSAMA-SAMA PADA PENGADILAN NEGERI SOLOK - Rifka Zuwanda; Rangga Prayitno (LPPM Universitas Ekasakti, 2021)
Fraud crimes have spread to the Solok Regency area by taking advantage of people's negligence towards technology, especially electronic social media, making it very easy for perpetrators of fraud crimes to carry out their plans by doing it together. Article 5 (3) Emergency Law Number 1 of 1951 concerning temporary measures to implement a unified structure of power and civil court procedures. One of the crimes that often occurs is the crime of fraud, this is because the crime of fraud is not difficult to carry out, just by relying on a person's ability to convince other people through a series of false or fictitious words, promises or giving lures in any form. , both for things that can provide magical powers and for wealth.